ҚЫТАЙ ТІЛІНДЕГІ ДИПЛОМАТИЯЛЫҚ ТЕРМИНДЕРДІҢ ӨЗІНДІК СИПАТТЫ БЕЛГІЛЕРІ - Токкарина, А. (Journal of Oriental Studies, 2016)
Автор статьи в своей работе рассматривает особенности дипломатических терминов китайского языка. In the article are studied the particularities of the diplomatic terms of chinese language.